PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KEKERASAN SEKSUAL BERDASARKAN UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASARAN SEKSUAL - Ramadhani, Muhammad Hadi (Journal of Law ( Jurnal Ilmu Hukum ), 2025)
ABSTRACT. Law Number 12 of 2022 on Sexual Violence Crimes (UU TPKS) is presented as a form of legal reform that provides legal certainty for victims and accommodates various aspects of protection, including the right to recovery, assistance, and guarantees to obtain justice. The research discusses the forms of legal protection for victims of sexual violence crimes according to Law Number 12 of 2022 on Sexual Violence Crimes and the obstacles in law enforcement related to the protection of victims of sexual violence based on the Law on Sexual Violence Crimes. The research findings indicate that legal protection for victims of sexual violence crimes according to Law Number 12 of 2022 includes various important aspects, ranging from physical and psychological protection to protection of the victim's identity and privacy. This law also pays special attention to the social and economic recovery of victims, as well as providing equal access to justice through legal assistance. The challenges in law enforcement related to the protection of victims of sexual violence based on Law Number 12 of 2022 are very complex and involve various aspects. Social and cultural factors that still regard sexual violence as a taboo issue, a complicated and time-consuming legal system, as well as limited accessibility of services, are the main obstacles in providing optimal protection for victims. Keywords: Legal Protection, Sexual Violence.